Predicting English Language Learners’ Proficiency Level Using EnglishScore Android Application - Anton, Oey; Yodi (Fakultas Komputer - Universitas Universal, 2021)
Teaching and learning the English language need to focus on the learners; therefore, as teachers, giving the range of materials and creating the study programs must be based on learners' ability to receive the learning progress in accordance. So, by revealing learners' abilities, teachers can organize their syllabus, material levels, quizzes, and other programs properly. CEFR is a British Council assessment used to know learners' abilities in several languages, including English. In this paper, we use EnglishScore android application to assess the learners' abilities based on CEFR scales. There are five categories of CEFR level scales that the learners of Universitas Universal academic year 2021-2022 provided: C1, B2, B1, A2, A1- using EnglishScore android application for assessment. Most learners acquire A2 level and B1 level with 40 and 28 percentages for overall skills. A2 and B1 with 40 and 28 percentages for grammar achievement, while B1, B2, and A2 for vocabulary achievement with 33, 27, and 26 percentages. A2 and B1 levels for reading and listening skills, with 42 and 23 percentages for reading skills and 39 and 22 for listening practice.